The effect of maceration duration on the total flavonoids content of kaempferia parviflora wall. ex baker ethanol extract - Leswara, Dianita Febrina; Sholehah I, Kholif; Kurniasih (MEDIA ILMU KESEHATAN, 2024)
Background: Kaempferia parviflora (Black ginger) has phytochemical compounds such as flavonoids, terpenoids, essential oils, and phenols that have the potential to treat various diseases. To maximize the total extracted flavonoids needs to optimize the extraction duration.Objective: Knowing the optimum maceration duration on the total flavonoid content using the UV-VIS Spectrophotometric method on black ginger ethanol extract.Method: Black ginger is extracted using the maceration method with ethanol (70%) solvent in maceration duration of 12, 24, 36,48, and 60 hours. The extract will be tested qualitatively and quantitative to determine the total levels of flavonoids using the UV-Vis Spectrophotometric method.Result: Qualitative test of black ginger ethanol extract gave positive results for flavonoids, phenolics, alkaloids, steroids, and tannins. The total level of flavonoids in black ginger ethanol extract was 7,8988 ? 0,1223 mgEQ/g (12 hours); 8,5705 ? 0,1529 mgEQ/g (24 hours); 9,8102 ? 0,0416 mgEQ/g (36 hours); 10,6161 ? 0,0768 mgEQ/g (48 hours); 7,2594 ? 0,1244 mgEQ/g (60 hours). The statistical analysis indicates a significant difference (p < 0,05) in the total flavonoid content at each maceration time. Conclusion: The duration of maceration time significantly affects the total flavonoid content produced with the optimum maceration time results at 48 hours